If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5p = -7p + 3p Combine like terms: -7p + 3p = -4p 6 + -5p = -4p Solving 6 + -5p = -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. 6 + -5p + 4p = -4p + 4p Combine like terms: -5p + 4p = -1p 6 + -1p = -4p + 4p Combine like terms: -4p + 4p = 0 6 + -1p = 0 Add '-6' to each side of the equation. 6 + -6 + -1p = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1p = 0 + -6 -1p = 0 + -6 Combine like terms: 0 + -6 = -6 -1p = -6 Divide each side by '-1'. p = 6 Simplifying p = 6
| 3(-2-3x)=-8x-4 | | y+0.4=0.6y+1.2 | | -128-8y=-48 | | 5n^2+5n=6 | | 5w=-5w+10w | | 2v^2-11v=v^2-14 | | 3(a-7)=21 | | 770=22w | | -20=x+7 | | 8x-9=2x+3 | | (6x+4)-(8x+8)= | | 0.7n-9+3=11-0.3n-15 | | 4g-3=-10 | | 0.5x+3=9.5 | | -4x^2-22x-10= | | 14+12x=11x-38 | | 11b=143 | | -4x-22x-10= | | 120=(2x+10)+(x+15) | | 7d+5=17.25 | | (5x+7)-(-3x+9)= | | -16x-8y=-48 | | 6-19b+10b^2= | | 25x^2-30x+9=36x^2 | | sin(2x)=sin(x) | | 6x+5=2x-8 | | 6x+7=x-22 | | 8a=120 | | 7(k-7)-(6k-1)=-8 | | (3x+9)+(-4x+3)= | | y-35=75 | | 4x^2-29x+19=-9x+10 |